THE IMPLEMENTATION OF READ, ANSWER, DISCUSS, EXPLAIN, AND CREATE (RADEC) LEARNING MODEL TO IMPROVE STUDENTS’ READING ABILITY AT THE ELEVENTH GRADE OF SMA PESANTREN PUTRI YATAMA MANDIRI - Anita; Ummi Khaerati Syam; Sitti Maryam Hamid (FKIP Unismuh Makassar, 2022)
This research aims to find out whether or not Read, Answer, Discuss, Explain, and Create (RADEC) learning model is effective to improve students’ reading ability in understanding a text at the eleventh grade of SMA Pesantren Putri Yatama Mandiri. The instrument of this research was a reading test about an explanation text consisted of 15 questions of multiple choice. This research used pre-experimental research that consisted of pre-test, treatment, and post-test. The population of this research was class XI A Regular that consisted of 20 students. The sample was selected by using a purposive sampling. The result of this research showed that the score of pre-test was 43.55 and post-test was 66.80. This research also showed the value of t-test was higher than the value of t-table (T-test > T-table). The value of t-test was 8.906 and the value of t-table was 2.093. It means that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. Based on the research result, the researcher concluded that the implementation of Read, Answer, Discuss, Explain, and Create (RADEC) learning model was effective to improve students’ reading ability.